2001
DOI: 10.1088/0953-2048/14/11/201
|View full text |Cite
|
Sign up to set email alerts
|

Review of the superconducting properties of MgB2

Abstract: This review paper illustrates the main normal and superconducting state properties of magnesium diboride, a material known since the early 1950s but only recently discovered to be superconductive at a remarkably high critical temperature T c = 40 K for a binary compound. What makes MgB 2 so special? Its high T c , simple crystal structure, large coherence lengths, high critical current densities and fields, and transparency of grain boundaries to current promise that MgB 2 will be a good material for both larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
672
4
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,135 publications
(764 citation statements)
references
References 179 publications
50
672
4
5
Order By: Relevance
“…4 compares the J c (B) variations of our samples for T ≥ 33 K. The undoped tape (Fig. 4a) shows approximately exponential J c (B) variation, which is typical for MgB 2 samples [2,10,14,20]. At low temperatures (high I c ), large self-field µ 0 H s (H s ≃ I c /c, where c is the circumference of the core) makes J c (B < µ 0 H s ) nearly constant, whereas at elevated fields (B → B irr ) J c rapidly decreases to zero.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…4 compares the J c (B) variations of our samples for T ≥ 33 K. The undoped tape (Fig. 4a) shows approximately exponential J c (B) variation, which is typical for MgB 2 samples [2,10,14,20]. At low temperatures (high I c ), large self-field µ 0 H s (H s ≃ I c /c, where c is the circumference of the core) makes J c (B < µ 0 H s ) nearly constant, whereas at elevated fields (B → B irr ) J c rapidly decreases to zero.…”
Section: Resultsmentioning
confidence: 82%
“…However, the onset of resistance (hence T c (R → 0) = T c0 ) is not affected by sheathing [25], and the zero-field T c0 = 38.2 K for the undoped tape ( Fig. 2a) is typical for bulk MgB 2 samples [2,5,24]. A strong shift of its T c0 with magnetic field (i.e.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The effects of doping MgB 2 with various elements such as s-elements Be [1] and Li [2], sp-elements Al [3,4] and Si [5], and d-elements F e, Co, Ni [6] and others [7] have been studied experimentally. Most of these substitutions take place in the Mg plane of MgB 2 , leaving the B plane in tact.…”
Section: Introductionmentioning
confidence: 99%
“…For some dopants at particular concentrations, it is also found that the dopants prefer to form a separate layer [3,4] rather than mix with the Mg layer or the B layer. For dilute amount of dopants the changes in the superconducting properties, in particular the superconducting transition temperature, T c , depends on the alloying element [1,2,3,4,5,6,7]. For larger concentrations, with only Mg 1−x Al x B 2 [3,4] being studied extensively, the T c is found to decrease due to the gradual filling of the B p x(y) -holes.…”
Section: Introductionmentioning
confidence: 99%